Remission: does it already exist in chronic rhinosinusitis with nasal polyposis? - Yvonne Chan; Andrew V. Thamboo; Joseph K. Han; Martin Desrosiers (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Remission, defined as absence of symptoms and objective markers of disease, is emerging as the penultimate goal in the management of several chronic diseases. The concept of remission, well-established in Rheumatology as well as Gastroenterology, is currently emerging in Respiratory Medicine for asthma. It is interesting to consider whether the disease remission concept might successfully be applied to Otolaryngology-Head and Neck Surgery in the management of chronic rhinosinusitis with nasal polyposis (CRSwNP). Objective The purpose of this letter is to explore the evidence supporting the concept of remission under continued medical therapy in chronic rhinosinusitis with nasal polyposis. Methods The authors reviewed the literature and summarized studies in chronic rhinosinusitis with nasal polyposis evaluating for evidence of clinical, biochemical, and endoscopic remission. Results Findings of the studies revealed that endoscopic sinus surgery with continued medical therapy achieved remission in approximately 50% of all patients. CRSwNP patients after primary endoscopic sinus surgery were able to achieve remission in 72% of instances, however this drops to 42% for patients having revision sinus surgery. For CRSwNP patients with co-morbidities such as asthma and aspirin exacerbated respiratory disease, remission rate drops to 23% and 23.5%, respectively compared to non-asthmatic CRSwNP patients who present a remission rate under continued medical therapy of 60%. Conclusion Remission of symptoms and evidence of disease under medical therapy is indeed a concept achievable in patients with CRSwNP, as demonstrated by studies in the literature. Various co-morbidities, notably asthma, apparently influence rate of remission. Better defining this outcome through consensus-based definitions will allow for the development of strategies in CRSwNP care that can help affected patients attain complete relief from clinical, biochemical, and endoscopic markers of CRS with judicious use of medication and surgery. Future efforts will attempt to improve on these outcomes by achieving symptomatic and endoscopic control of disease following cessation of therapy, potentially paving the way towards clinical remission or a ‘cure’ in CRS.